Trunk angular velocity: A convenient, valid and responsive substitute for force plate-based measures of dynamic postural stability - Lammert A. Vos; Maarten R. Prins; Elien Plompen; Jaap H. van Dieën; Idsart Kingma (PLoS ONE, 2025)
Objective Deficits in dynamic postural stability are associated with increased risk of lower limb injuries. Objective dynamic postural stability assessments typically require force plates, which are not commonly available in the clinic. Moreover, these outcomes are not directly related to balance strategies, which hampers clinical interpretation and translation to therapeutic goals. Direct measurements of kinematics can be more suitable in these respects. This study aims to investigate the concurrent validity and responsiveness of trunk angular velocity. Methods Data from fourteen healthy participants were analyzed using a within-subject design. Participants were standing on one leg on a platform with an embedded force plate that was used to impose mediolateral perturbations to evoke balance responses. To introduce variability within participants, perturbation amplitude and base-of-support width were manipulated. Time-to-stability, mean center of pressure speed and the mean vertical force deviation of the ground reaction force were derived from force plate data and mean trunk angular velocity was obtained from an inertial measurement unit. All outcomes were calculated over a five-second time window after perturbation onset. Multilevel correlations were calculated to assess the concurrent validity of trunk angular velocity. To compare the responsiveness of trunk angular velocity and force plate-based outcomes, effect sizes of a repeated measures ANOVA were used. Results Trunk angular velocity correlated strongly with center of pressure speed (r = 0.78) and the vertical force deviation (r = 0.74) and moderately with time-to-stability (r = 0.61). Trunk angular velocity demonstrated the largest effect sizes in the repeated measures ANOVA. Conclusion Trunk angular velocity is a promising outcome to use in the clinic. Its concurrent validity and responsiveness are supported by the results of this study.